Organic farming is the agriculture of XXI century - Pysarenko, V.; Pysarenko, P. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The data are given about forty years old experience in private enterprise «Agroecology» in the horticulture branch was provided. The wide improving of them allows to receive the high yields of grain crops, ecologically friendly production, increase the soil fertility.